Cost-effectiveness analysis of serplulimab plus chemotherapy in the first-line treatment for PD-L1-positive esophageal squamous cell carcinoma in China - Liu, Shixian; Jiang, Nana; Dou, Lei; Li, Shunping (Frontiers in Immunology, 2023)
Objective: The ASTRUM-007 trial (NCT03958890) demonstrated that serplulimab plus chemotherapy administered every 2-week significantly improved progression-free and overall survival in patients with previously untreated, programmed death-ligand 1 (PD-L1) positive advanced esophageal squamous-cell carcinoma (ESCC). This study was aimed to investigate the cost-effectiveness of serplulimab plus chemotherapy in the first-line treatment of PD-L1-positive advanced ESCC. Methods: A partitioned survival model with a 2-week cycle and a 10-year time horizon was constructed from the Chinese healthcare system perspective. The survival data, direct medical costs and utilities were derived from the ASTRUM-007 trial and published sources. Total costs, quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratios (ICERs) were calculated. Scenario, one-way and probabilistic sensitivity analyses were performed to assess the uncertainty around model parameters. Results: Compared with chemotherapy, serplulimab plus chemotherapy provided additional 0.27 QALYs with an incremental cost of $33,460.86, which had an ICER of $124,483.07 per QALY. The subgroup analyses revealed that the ICERs of serplulimab plus chemotherapy were $134,637.42 and $105,589.71 in advanced ESCC patients with 1 ≤ CPS < 10 and CPS ≥ 10, respectively. The price of serplulimab, patient weight, utility values and discount rate were the most influential parameters on base-case results. At a willingness-to-pay threshold of three times per capita GDP ($38,351.20) in 2021, the probability of serplulimab plus chemotherapy being cost-effective was 0% compared with chemotherapy. When the price of serplulimab decreased by 70%, the probabilities of serplulimab plus chemotherapy being cost-effective were 72.10%, 55.24% and 93.23% in advanced ESCC patients with PD-L1-positive, PD-L1 1≤CPS<10 and CPS≥10, respectively. Conclusion: Serplulimab plus chemotherapy in the first-line treatment for PD-L1-positive advanced ESCC might not be cost-effective in China.